Challenges for Soviet-American collaboration in the Cold War: the capitalisation of pianist Sviatoslav Richter for American musical markets. Issue 2 (3rd April 2019) - Herrala, Meri Elisabet
ABSTRACT: This article introduces a rarely covered topic in Cold War research – the superpower collaboration and competition to sell and distribute Soviet classical music recordings in America. While analysing the case of pianist Sviatoslav Richter's 'bootlegged' recitals at Carnegie Hall in October 1960, this article discusses the challenges for Soviet-American collaboration in capitalising Richter's intellectual property for American musical markets. The case of the unauthorised sale of Richter's recordings shows how the American entrepreneurs used the Soviet government's inexperience in the capitalist environment. It ultimately became necessary for the Soviet government to take part in capitalist speculation.